Near-complete genome sequences of Nine SARS-CoV-2 strains harboring the D614G mutation in Malaysia - Ummu Afeera, Zainulabid; Norhidayah, Kamarudin; Ahmad Hafiz, Zulkifly; Gan, Han Ming; Tay, Darren Dean; Siew, Shing Wei; Aini Syahida, Mat Yassim; Sharmeen Nellisa, Soffian; Ahmad Afif, Mohd Faudzi; Ahmad Mahfuz, Gazali; Gaanty Pragas, Maniam; Hajar Fauzan, Ahmad (ASM Journals, 2021)
Here, we report the nearly complete genome sequences of nine SARS-CoV-2 variants with the D614G mutation. These viruses were detected from various infected individuals with different levels of severity from Pahang, Malaysia. In addition, this study described the presence of lineage B.1.351 as a type of variant of concern (VOC), lineage B.1.466.2, and lineage B.1.524 as a local variant. Here, we report the nearly complete genome sequences of nine severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants with the D614G mutation. These viruses were detected from various infected individuals with different levels of severity from Pahang, Malaysia. In addition, this study described the presence of lineage B.1.351 as a type of variant of concern (VOC) and lineages B.1.466.2 and B.1.524 as local variants.